2014
DOI: 10.1016/j.eplepsyres.2014.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Auditory event-related potentials in children with benign epilepsy with centro-temporal spikes

Abstract: Summary Benign focal epilepsy in childhood with centro-temporal spikes (BECTS) is one of the most common forms of idiopathic epilepsy, with onset from age 3 to 14 years. Although the prognosis for children with BECTS is excellent, some studies have revealed neuropsychological deficits in many domains, including language. Auditory event-related potentials (AERPs) reflect activation of different neuronal populations and are suggested to contribute to the evaluation of auditory discrimination (N1), attention allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…The frontal lobe is known to play a major role in the processing and execution of higher cognitive skills and behaviors (Stuss, 2011 ) and children with benign epilepsy have been found to present cognitive deficits and impaired mental activity (Ay et al, 2009 ; Datta et al, 2013 ; Verrotti et al, 2014 ). Furthermore, the right auditory network, including right temporal, parietal and left auditory cortex (in θ band), also showed altered (higher) functional integration (network degree) in patients, which could affect auditory processing in both hemispheres, resulting in language processing deficits in BECTS patients (Naganuma et al, 1994 ; Tomé et al, 2014 ; Filippini et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The frontal lobe is known to play a major role in the processing and execution of higher cognitive skills and behaviors (Stuss, 2011 ) and children with benign epilepsy have been found to present cognitive deficits and impaired mental activity (Ay et al, 2009 ; Datta et al, 2013 ; Verrotti et al, 2014 ). Furthermore, the right auditory network, including right temporal, parietal and left auditory cortex (in θ band), also showed altered (higher) functional integration (network degree) in patients, which could affect auditory processing in both hemispheres, resulting in language processing deficits in BECTS patients (Naganuma et al, 1994 ; Tomé et al, 2014 ; Filippini et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged N19-P25 interval has, however been reported in patients with idiopathic generalized epilepsy (IGE) using median nerve stimulation ( Salas-Puig et al, 1992 ). Both visual ( Verleger et al, 1997 ) and auditory delays ( Tome et al, 2014 ) have been observed in the evoked responses of adults and children with epilepsy. We speculate that the influence of anti-epileptic medications may be a contributing factor in promoting the tactile P50m latency delay in our epilepsy group (see Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…[66,67]). Za pomocą CAEP próbuje się obiektywnie oceniać funkcjonowanie różnego rodzaju procesów poznawczych w chorobach związanych z nieprawidłowym działaniem ośrodkowego układu nerwowego, takich jak chociażby: epilepsja [68], udar mózgu [69], śpiączka [70], zespół alkoholowy [71], depresja, schizofrenia [66], choroba Alzheimera [72] czy chociażby różnego rodzaju formy demencji [73]. Naturalnym polem klinicznego wykorzystania słuchowych potencjałów korowych pozostaje jednak od lat przede wszystkim audiologia.…”
Section: Cel Pracyunclassified
“…Ponadto warto zaznaczyć, iż w znacznej większości dostępnych prac fala N2 bywa z reguły rozpatrywana nie jako pojedyncza składowa, lecz jej zmiany analizowane są wraz z innymi komponentami CAEP, zarówno egzogennymi, jak i endogennymi (np. [34,68,179]). Trzeba również podkreślić, że większość badań dotyczących składowej N2 CAEP wykonywana była w schematach doświadczalnych wykorzystujących bodźce wzrokowe, a nie słuchowe (przegląd patrz np.…”
Section: Fala N2unclassified